Optimalisasi limbah serbuk besi dan superplasticizer terhadap workability kuat tekan beton berkelanjutan - Sartika Nisumanti; Rahmat Shafari Abdillah; Marguan Fauzi (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2026)
The utilization of industrial waste as a concrete constituent material is an important strategy to reduce the use of natural fine aggregates and support the development of sustainable concrete materials. This study aims to evaluate the effect of iron powder as a partial substitute for fine aggregate combined with 0.8% superplasticizer on setting time, workability, density, and compressive strength of concrete with a target strength of fc’ 20 MPa. The method was conducted experimentally and consisted of six mixture variations, namely normal concrete, concrete with 4% iron powder, concrete with 0.8% superplasticizer, and concrete with 4%, 5%, and 6% iron powder combined with 0.8% superplasticizer. The test specimens were prepared as cylinders measuring 10 cm x 20 cm and tested at 7, 14, and 28 days, while the characteristics of the aggregate, slump, setting time, density, and compressive strength were analyzed descriptively and comparatively. The research results show that the mixture of 6% iron powder and 0.8% superplasticizer produced the highest 28-day compressive strength of 25.5 MPa, an increase of about 18% compared to normal concrete at 21.39 MPa. This indicates that substituting local low-content iron powder waste, combined with a superplasticizer, can enhance compressive strength while maintaining concrete workability. This research can provide a practical foundation for the development of sustainable concrete based on local industrial waste.